IMPROVEMENT OF THE DRIVE OF THE DRYER 2SB-10 IN ORDER TO REDUCE ITS ENERGY CONSUMPTION - R.K. Jamolov; A.M. Shodmonkulov (Journals Park Publishing, 2022)
The article presents the results of research work carried out at Paxtasanoatilmiymarkazi (cotton industry scientific center) JSC to improve the drive of the 2SB-10 drum-type cotton dryer. A scheme of a new chain drive has been developed, the leading part of the developed drive has been manufactured and tested in the conditions of the scientific center.
Keywords: dryer drum; drive; chain drive